Servants of Ganesh: Review of Servants of Ganesh: Inside The Elephant Stable, dir. Mark Dugas & Piers Locke - Rothfels, Nigel (Humanimalia, 2010)
Review of Servants of Ganesh: Inside The Elephant Stable (2006). Mark Dugas (Producer, Writer, Camera, Editor); Piers Locke (Anthropological Consultant, Co-Producer). Ethnographic Documentary. DVD format. 42 minutes.